Emerging Strategies to Improve the Design and Manufacturing of Biocompatible Therapeutic Materials - Guillermo Martínez; Juan Vázquez; Belén Begines; Ana Alcudia (MDPI AG, 2023)
Currently, the field of medicine is drastically advancing, mainly due to the progress in emerging areas such as nanomedicine, regenerative medicine, and personalized medicine. For example, the development of novel drug delivery systems in the form of nanoparticles is improving the liberation, absorption, distribution, metabolism, and excretion (LADME) properties of the derived formulations, with a consequent enhancement in the treatment efficacy, a reduction in the secondary effects, and an increase in compliance with the dosage guidelines. Additionally, the use of biocompatible scaffolds is translating into the possibility of regenerating biological tissues. Personalized medicine is also benefiting from the advantages offered by additive manufacturing. However, all these areas have in common the need to develop novel materials or composites that fulfill the requirements of each application. Therefore, the aim of this Special Issue was to identify novel materials/composites that have been developed with specific characteristics for the designed biomedical application.